Proceedings of the 2024 2nd International Conference on Management Innovation and Economy Development (MIED 2024) - Barbara Siuta-Tokarska; Adriana Grigorescu; Yifeng Zhu (Atlantis Press International BV, 2024)
This book is open access. Economic development is one of the necessary conditions for social development, and management innovation is an inherent attribute of societies, countries, governments, and enterprises. With the advent of globalization in the 21st century, enterprises, governments, countries and other organizational units have put forward higher requirements for management innovation, and economic development is seeing major challenges. The 2nd International Conference on Management Innovation and Economic Development ( MIED 2024) will be held in Guilin, China on June 28-30, 2024. The conference aims to provide a platform for experts, scholars, engineering technicians, and technical R&D personnel engaged in the research of economics and management to share scientific research achievements and cutting-edge technologies, understand academic development trends, broaden research ideas, strengthen academic research and exploration, and promote cooperation in the industrialization of academic achievements. The conference cordially invites experts, scholars, business professionals, and other relevant personnel from domestic and foreign universities, research institutions, and other relevant personnel to participate and exchange ideas! We cordially invite you to submit papers and look forward to meeting you in MIED 2024!